2018
DOI: 10.1093/neuonc/noy093
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms based on preoperative multiparametric magnetic resonance imaging for prediction of molecular subgrouping in medulloblastoma: results from a radiogenomics study of 111 patients

Abstract: The predictive accuracy of MRI-based nomograms was excellent for SHH and encouraging for Group 4 medulloblastoma. Further work is needed for Group 3 and WNT-pathway medulloblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 25 publications
0
62
0
Order By: Relevance
“…In their cohort of adult WNT-pathway medulloblastoma, Zhao et al [28] found significant contrast enhancement in all 17 patients, which was either heterogeneous (82%) or solid (18%). In their cohort of 17 patients with WNT-pathway medulloblastoma, Dasgupta et al [31] reported intense contrast enhancement in all patients; 53% showed homogeneous enhancement, while the enhancement pattern was inhomogeneous in the remaining 47% of patients.…”
Section: Contrast-enhancement Patternmentioning
confidence: 97%
See 4 more Smart Citations
“…In their cohort of adult WNT-pathway medulloblastoma, Zhao et al [28] found significant contrast enhancement in all 17 patients, which was either heterogeneous (82%) or solid (18%). In their cohort of 17 patients with WNT-pathway medulloblastoma, Dasgupta et al [31] reported intense contrast enhancement in all patients; 53% showed homogeneous enhancement, while the enhancement pattern was inhomogeneous in the remaining 47% of patients.…”
Section: Contrast-enhancement Patternmentioning
confidence: 97%
“…In the last decade or so, several investigators from across the world have tried to correlate semantic imaging features with molecular subgrouping in medulloblastoma. All such studies [21][22][23][24][25][26][27][28][29][30][31] reporting on the imaging genomics of medulloblastoma are briefly summarized in Table 1. While it is quite clear that no single imaging feature is pathognomonic of any particular subgroup, certain imaging characteristics are much more prevalent in one subgroup compared to others and may even be highly specific for an individual molecular subgroup.…”
Section: Specific Imaging Features In Medulloblastoma Subgroupsmentioning
confidence: 99%
See 3 more Smart Citations